EFEKTIFITAS PEMBERIAN PERMEN JAHE TERHADAP MUAL MUNTAH PADA IBU HAMIL DI KLINIK KHAIRUNIDA SUNGGAL TAHUN 2018 - Nurdiana, Ani; Mangkuji, Betty; Lubis, Rismahara (Poltekkes Kemenkes Medan, 2019)
Pregnancy causes a lot of change in the mother’s body, so there are various kinds of physiological discomfort in the mother such as nause and vomiting, usually mild and controlable. This condition sometimes stops in the first trimester, but its effect may lead to nutritional disorder, dehydration, weakness, weight loss, and electrolyte imbalances. If not treated, it will worsen into Hyperemesis Gravidarum This study aimed to determine the effectiveness og ginger candy in reducing the frecuency of nause and vomiting in first trimester pregnant women in the Khairunida clinik with experimental Quasy design and tested by One Group Pretest Postest. About 15 samples were obtained through purposive sampling technique and the data were taken using the T-dependent test. Through the study, it was found that the frequency of nausea and vomiting before being given intervation was 10,93 and after being given intervation was 3,33 with an average decrease by 7,60. Through the statistical test, it was obtained the p value <(0.05) so that this study concluded that administration of ginger candy was effective in reduring nausea and vomiting in first trimester pregnant women. Further researchers are expected toreduce the use of non-pharmacological drugs to overcome nausea and vomiting in first trimester pregnant women and collaborate with the pharmacy department to facilitate the process of making good qualityy ginger candy.